2020
DOI: 10.1007/s11244-020-01378-w
|View full text |Cite
|
Sign up to set email alerts
|

C, N Co-Decorated Alumina-Supported Au Nanoparticles: Enhanced Catalytic Performance for Selective Hydrogenation of Acetylene

Abstract: The modifications of support for the dispersion and immobilization of gold nanoparticles were examined for the selective hydrogenation of acetylene to ethylene. The catalyst, denoted as Au/CNA, was prepared by the carbonization of C and N atom-containing organic precursors on Al 2 O 3 , which were subsequently used as supports for gold nanoparticles. The TOF value of Au/CNA was five times higher than that of Au/Al 2 O 3 at 250 °C. The carbonization modification of Al 2 O 3 support without N species showed almo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…X. Sun et al have previously reported that, since acetylene belongs to the acidic molecules, the alkaline nature of the catalyst surface has a positive effect on the adsorption of acetylene on the Au surface, which can lead to a better catalytic performance of the catalyst [49]. Therefore, it was hypothesized that a higher base/acid ratio has an auxiliary effect on the adsorption of acetylene at the perimeter of Au nanoparticles, which is a potential reason for the higher acetylene conversion of the Au/CuMgAlO x catalyst.…”
Section: Acid-base Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…X. Sun et al have previously reported that, since acetylene belongs to the acidic molecules, the alkaline nature of the catalyst surface has a positive effect on the adsorption of acetylene on the Au surface, which can lead to a better catalytic performance of the catalyst [49]. Therefore, it was hypothesized that a higher base/acid ratio has an auxiliary effect on the adsorption of acetylene at the perimeter of Au nanoparticles, which is a potential reason for the higher acetylene conversion of the Au/CuMgAlO x catalyst.…”
Section: Acid-base Propertymentioning
confidence: 99%
“…Y. Zhang et al reported strong interactions between the N species on the support and Au nanoparticles, and the TOF value of Au/CNA was five times higher than that of Au/Al 2 O 3 [49]. L. Sun et al added CeO 2 to Au/Al 2 O 3 catalysts to change the acidbase properties of the support surface and electronic states of the Au species to improve catalytic activity [50].…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue of Topics in Catalysis contains a selection of contributions from the participants in CatET-2019. The selected articles [ 1 9 ], which went through a rigorous peer-review process, represent the most interesting topics addressed at the congress.…”
mentioning
confidence: 99%
“…Gold catalysts are the protagonists of articles [ 1 3 ]. Gold nanoparticles supported on C and N co-decorated alumina [ 1 ] and on Ce–Zr oxides [ 2 ] were investigated for selective hydrogenation of acetylene, and polyaniline microtubes have been proposed as a support for gold nanoparticles to improve the catalytic performance in reduction of nitrophenols [ 3 ].…”
mentioning
confidence: 99%